2018
DOI: 10.1016/j.actatropica.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii in dairy goats with a history of reproductive disorders in Brazil

Abstract: Coxiella burnetii, an intracellular bacterium, is the agent of Q fever/coxiellosis, a worldwide zoonosis. Dairy animals are the primary reservoirs of C. burnetii, and although the disease is usually asymptomatic or subclinical, abortion is a serious clinical outcome among small ruminants. This study was conducted to investigate C. burnetii seroprevalence and infection In a flock of dairy goats in Brazil. Serum samples from 312 goats collected from a dairy goat flock with a history of reproductive failure were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 31 publications
1
22
0
2
Order By: Relevance
“…The presence of novel MST and MLVA genotypes of C. burnetii in Brazil and Argentina raises the question of the importance of different lineages of C. burnetii in animal and human cases of Q fever, with a necessity of virulence studies to elucidate this question. The report of abortion in goats due to C. burnetii [22] and Q fever in humans in Brazil and Argentina [23][24][25][26] indicates the presence of virulent strains circulating in those countries. This is the first genotype study of Coxiella strains from Brazil and Argentina using MST and MLVA, molecular tools commonly used for this pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of novel MST and MLVA genotypes of C. burnetii in Brazil and Argentina raises the question of the importance of different lineages of C. burnetii in animal and human cases of Q fever, with a necessity of virulence studies to elucidate this question. The report of abortion in goats due to C. burnetii [22] and Q fever in humans in Brazil and Argentina [23][24][25][26] indicates the presence of virulent strains circulating in those countries. This is the first genotype study of Coxiella strains from Brazil and Argentina using MST and MLVA, molecular tools commonly used for this pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the low rate of seropositivity found for C. burnetii (13.7%, 14/102) among the sampled bovine population with reproductive disorders, it should be noted that most (71.4%, 10/14) of the seropositive animals showed high antibody titers, ranging from 512 to 131072. Even though high antibody titers are suggestive of recent infection (GUIMARÃES et al, 2017;OLIVEIRA et al, 2018), the antigen used in the present study is only reactive to phase-1 antibodies, found only in the chronic phase of the disease (PEACOCK et al, 1983). Therefore, it is possible that the seropositive animals were in the chronic phase of the disease at the time of sampling.…”
Section: Discussionmentioning
confidence: 61%
“…Although serological evidence of exposure to C. burnetii has already been reported in cattle in Europe (CZAPLICKI et al, 2009;AGGER et al, 2010;BOTTCHER et al, 2011;GACHE et al, 2017;RYAN et al, 2018;VARELA-CASTRO et al, 2018;VIDAL et al, 2017;SOFTIC et al, 2018), Asia (CETINKAYA et al, 2000NOKHODIAN et al, 2016), North America (MCQUISTON et al, 2005 and Africa (KAMGA-WALADJO et al, 2010;SCOLAMACCHIA et al, 2010), there are few data on seroprevalence to this agent in ruminants in Brazil. In this regard, while Guimarães et al (2017) found a seropositivity rate of 2% for C. burnetii among sheep sampled in the state of Piauí, northeast of Brazil, Oliveira et al (2018) found a seroprevalence of 55.1% in a herd of goats with history of reproductive disorders in the state of Alagoas, Northeast of Brazil. Recently, Souza et al (2018) found 2.2% of the goats and 2.1% of the sheep seropositive to C. burnetii in the state of Pernambuco, also in northeastern Brazil.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations